The Strategic Importance of Supplier Relationships in the Automotive Industry. (19th June 2013) - Brandes, Ove; Brege, Staffan; Brehmer, Per-Olof
The aim of this paper is to analyse longitudinally the development of purchasing strategies in the automotive industry during the last 20 years. The amplitude of the business cycle during this time frame has been very high and includes periods of financial/automotive crisis as well as high sales and demand. Our empirical data is primarily drawn from a 1990–2010 longitudinal case study of the relationship between automaker Volvo Personal Cars and Autoliv, a supplier of seat belts and airbags, complemented with secondary data framing the development of the industry level. The theoretical focus is on outsourcing and purchasing strategies developed within long-lasting buyer-supplier relationships; theoretical pillars are found in transaction-cost theories and the resource-based view of the firm. Based on the longitudinal case study, our analysis pinpoints the importance of intimate cooperation between customer and supplier in areas close to the core values and core competences of the buyer (that is, the automaker). From an industry-level perspective, the winners in the automobile industry from 2010 and onwards have been and will be those who can organize long-term collaboration partnerships between the automakers, their suppliers, and the political stakeholders, and who can outsource a large part of the technical development to the suppliers in areas also close to the core competences. The automakers must accept that their suppliers have competing automakers as their customers and search for synergies in their product portfolio. Theoretically, there is a need for conceptual development through deeper studies of the firm's relational capability and its implications.